The handbook of English linguistics - Hinrichs, Lars; McMahon, April M. S.; Aarts, Bas 1961- (John Wiley & Sons Ltd., 2020)
The second edition of the popular Handbook of English Linguistics brings together stimulating discussions of the core topics in English linguistics in a single, authoritative volume. Written by an international team of experts, the chapters cover syntax, methodology, phonetics and phonology, lexis and morphology, variation, stylistics, and discourse, and also provide discussions of theoretical and descriptive research in the field.